Reduction of caveolin and caveolae in oncogenically transformed cells. - Koleske, A J (1995)
Caveolae are flask-shaped non-clathrin-coated invaginations of the plasma membrane. In addition to the demonstrated roles for caveolae in potocytosis and transcytosis, caveolae may regulate the transduction of signals from the plasma membrane. Transformation of NIH 3T3 cells by various oncogenes leads to reductions in cellular levels of caveolin, a principal component of the protein coat of caveolae. The reduction in caveolin correlates very well with the size of colonies formed by these transformed cells when grown in soft agar. Electron microscopy reveals that caveolae are morphologically absent from these transformed cell lines. These observations suggest that functional alterations in caveolae may play a critical role in oncogenic transformation, perhaps by disrupting contact inhibition in transformed cells.